Cruel Children in Popular Texts and Cultures (Critical Approaches to Children's Literature, 2018)
This book explores how alarmist social discourses about 'cruel' young people fail to recognize the complexity of cruelty and the role it plays in child agency. Examining representations of cruel young people in popular texts and popular culture, the collected essays demonstrate how gender, race, and class influence who gets labeled 'cruel' and which actions are viewed as negative, aggressive, and disruptive. It shows how representations of cruel young people negotiate the violence that shadows polite society, and how narratives of cruelty and aggression are used to affirm, or to deny, young people's agency.